Role of bone morphogenetic proteins in periodontal regeneration- a review - Potharaju, Santhi Priya; Prathypaty, Santha Kumari; Chintala, Ravi Kanth; Yendluri, Durga Bai; Kolliboyana, Jai Krishna Srikanth (International Journal of Health, 2016)
Bone Morphogenetic Proteins (BMPs) are multifunctional growth factors and have the unique property of inducing stem and mesenchymal cell differentiation in to osteogenic cells, capable of producing bone. They are categorized under the super family Transforming Growth Factor-Î² (TGF-Î²). In the concept of tissue engineering they are the first approved therapeutic proteins to be used in conjunction with a scaffold and a biocompatible fixative device. Thus in this review the mechanism of action of BMPs is described at its cellular and molecular levels along with its potential clinical applications, utilization perspectives and scientific evidence in periodontal regeneration.